2011
DOI: 10.1111/j.1911-3838.2011.00024.x
|View full text |Cite
|
Sign up to set email alerts
|

Annual Reporting and Accountability by Municipalities in Canada: An Empirical Investigation*

Abstract: Prior research regarding reporting and accountability by local governments in several countries has questioned the value of traditional annual reporting and the level of accountability to the public. This article reports on comparable research for local governments throughout Canada. The disclosure index methodology is used to evaluate the quality and quantity of information published in the annual reports and in the financial statements of Canadian local governments in 2003 with a comparison in 2005. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
0
12
0
1
Order By: Relevance
“…Lynch, 2010;Schneider & Samkin, 2008), followed by the US/Canada with 9 (e.g., Blanco, Lennard, & Lamontagne, 2011;Fischer, Gordon, & Kraut, 2010). Compared with other regions, Europe as a research site is less investigated with only seven articles (e.g.…”
Section: Country Of Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Lynch, 2010;Schneider & Samkin, 2008), followed by the US/Canada with 9 (e.g., Blanco, Lennard, & Lamontagne, 2011;Fischer, Gordon, & Kraut, 2010). Compared with other regions, Europe as a research site is less investigated with only seven articles (e.g.…”
Section: Country Of Researchmentioning
confidence: 99%
“…Seven articles considered one or more sections of the annual report (Allini et al, 2016;Blanco et al, 2011;de Deus & de Mendonça, 2015;Fischer et al, 2010;Guo, Fink, & Frank, 2009;Kaur & Arora, 2013;Robbins & Austin, 1986); while three papers concern specific issues such as disclosure regarding single financial statements' items (Bunget, Blidisel, Feleaga, & Popa, 2014;Giroux, 1989;Vermeer, Styles, & Patton, 2012). Five of these studies (Allini et al, 2016;de Deus & de Mendonça, 2015;Kaur & Arora, 2013;Robbins & Austin, 1986; ijbm.ccsenet.org…”
Section: External Reporting: Disclosure Of Financial Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies focused on accountability disclosures in other settings. Among these few were Ryan et al (2002) and Blanco et al (2011) who studied Australian and Canadian local governments' annual reports respectively. Herawaty and Hoque (2007) focused on Australian governmental departments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Blanco et al (2011) and Banks et al (1997) reported an overall low disclosure index on information published in the annual reports of Canadian local governments and universities in England, Wales, and Northern Ireland, respectively. More specifically, certain disclosure areas such as human resources and asset management showed low levels of disclosure, as reported by Herawaty and Hoque (2007) and Schneider and Samkin (2008).…”
Section: Literature Reviewmentioning
confidence: 99%